The Warner boys [compact disc, unabridged] : our family's story of autism and hope - Warner, Ana; Warner, Curt; Boling, Dave (Brilliance Audio, 2018)
Seahawks star Curt Warner and his wife, Ana, were prominent figures in 1990s Seattle. When Curt retired, everyone assumed it was for a simpler life. The reality behind their seclusion was a secret: their twins, Austin and Christian, had been diagnosed with severe autism. What followed was a painful struggle to hold their family and their marriage together in a home filled with chaos, emotional exhaustion, and constant fear for the safety of their unpredictable but beloved boys.